Tracking the Lionfish (Pterois miles) invasion through public engagement: new records and implications for Species Distribution Models in the Mediterranean Sea - AZZURRO, ERNESTO; FALAUTANO, MANUELA; CASTRIOTA, LUCA; CHIAPPI, MARINA; D’AMEN, MANUELA; LUNETTA, ALESSIA; INTERDONATO, FILIPPO; SPINELLI, ANDREA; TIRALONGO, FRANCESCO (Mediterranean Marine Science, 2025)
A comprehensive update on the distribution of lionfish (Pterois miles) in the Mediterranean Sea was conducted by documenting 16 newly confirmed photographic records from southern Italy, collected through a national alert campaign supported by three Italian ministries. The campaign, titled Attenti a quei 4! (“Beware of those 4!”), also led to the detection of other invasive species, although lionfish were the most frequently recorded. These new observations, along with 60 georeferenced records from recent scientific literature, were integrated into the www.ormef.eu dataset, resulting in the most up-to-date compilation of P. miles records in the Mediterranean as of March 2025. This updated dataset, now comprising a total of 1,840 georeferenced records, was visualized in a distribution map and compared with predictions made by previously published species distribution models. Notably, most new occurrences were concentrated in the Ionian Sea, a region where climate change projections had previously identified a high risk of invasion for this tropical species. These findings offer valuable insights into the ongoing expansion of P. miles, lending support to model predictions of high-risk areas.